Monitoring of Water Quality for Reduced Water Use in a Partial Recirculating Aquaculture System - Lindholm‐Lehto, Petra Camilla; Sinisalo, Kalle; Pulkkinen, Jani Tapio; Kiuru, Tapio (John Wiley & Sons, 2025)
Partial recirculating aquaculture systems (PRASs) aim for combining the benefits of flow-through systems (water use of approximately 50,000 L kg−1 feed) and recirculating aquaculture systems (RASs, 500–1000 L kg−1 feed). While water quality is usually excellent in flow-through systems, large volumes of water of good quality are required. In RAS, investment and production costs can be high, and due to the microbial actions typically occurring in RAS, off-flavours can occur and accumulate in fish flesh. Here, an evaluation between three water renewal rates (4000, 2000 and 1000 L kg−1 feed) of a PRAS was performed. In the experiment, rainbow trout Oncorhynchus mykiss was reared in similar PRASs. Fish growth and a variety of water quality parameters were monitored, including 14 off-flavour compounds in the recirculating water, in the inlet water and in fish flesh. The results did not show statistical differences in feed conversion ratio (FCR), specific growth rate (SGR), and mortality between water renewal of 2000 and 4000 L kg−1 feed, while reduced growth was observed at 1000 L kg−1 feed. Additionally, total ammonia nitrogen (TAN) and nitrite–nitrogen (NO2─N) increased at reduced water renewal rates of 1000 and 2000 L kg−1 feed (p < 0.005). Concentrations of off-flavours remained low in the circulating water, but in the circulating water and in fish flesh, they were above the known sensory thresholds at 1000 L kg−1. Overall, the results suggest that 2000 L kg−1 feed offers good fish growth, feed use and low mortality without the unwanted off-flavour accumulation.
Keywords: hydrogen peroxide; off-flavors; partial recirculating aquaculture system (PRAS); rainbow trout; total ammonia nitrogen (TAN)